TULAK BALA SEBAGAI TRADISI MASYARAKAT ACEH DALAM MENGHADAPI VIRUS CORONA - Saputra, Teuku Amnar; Zuriah, Zuriah (JURNAL AL-IJTIMAIYYAH, 2020)
In responding to the corona virus outbreak, each region has a different way. Aceh, which is identical to Islamic law, also has a different way of dealing with the Corona Virus Outbreak. One of the ways that the Acehnese people do is to revive the Tulak Bala tradition. This study aims to examine how an outbreak is in the historical perspective of the Acehnese people and how the Tulak Bala Tradition is carried out by the people of Aceh in dealing with the Corona Virus. This type of research is qualitative research with a phenomenological approach. Data collection was carried out by means of observation, documentation and interviews and data presentation was carried out descriptively. The results showed that an epidemic was not something new for the people of Aceh. The epidemic has occurred since the 2nd Dutch aggression with the spread of a cholera epidemic that killed many people. The Tulak Bala tradition carried out by the people of Aceh is a tradition that has been passed down from generation to generation to its predecessors. This tradition does not believe that it can prevent and eliminate all forms of plague and calamity. The people of Aceh believe that the plague is an offering of Allah SWT so that to be able to deal with it, they must ask for help from the Creator.Keywords: Aceh Community, Tradition, Tulak Bala, and Corona Virus.